Genomic divergence in cotton germplasm related to maturity and heterosis. Issue 8 (19th December 2018) - He, Shoupu; Sun, Gaofei; Huang, Longyu; Yang, Daigang; Dai, Panhong; Zhou, Dayun; Wu, Yuzhen; Ma, Xiongfeng; Du, Xiongming; Wei, Shoujun; Peng, Jun; Kuang, Meng
Abstract: Commercial varieties of upland cotton ( Gossypium hirsutum ) have undergone extensive breeding for agronomic traits, such as fiber quality, disease resistance, and yield. Cotton breeding programs have widely used Chinese upland cotton source germplasm (CUCSG) with excellent agronomic traits. A better understanding of the genetic diversity and genomic characteristics of these accessions could accelerate the identification of desirable alleles. Here, we analyzed 10, 522 high‐quality single‐nucleotide polymorphisms (SNP) with the CottonSNP63K microarray in 137 cotton accessions (including 12 hybrids of upland cotton). These data were used to investigate the genetic diversity, population structure, and genomic characteristics of each population and the contribution of these loci to heterosis. Three subgroups were identified, in agreement with their known pedigrees, geographical distributions, and times since introduction. For each group, we identified lineage‐specific genomic divergence regions, which potentially harbor key alleles that determine the characteristics of each group, such as early maturity‐related loci. Investigation of the distribution of heterozygous loci, among 12 commercial cotton hybrids, revealed a potential role for these regions in heterosis. Our study provides insight into the population structure of upland cotton germplasm. Furthermore, the overlap between lineage‐specific regions and heterozygous loci, in the high‐yield hybrids, suggests a role for these regions in cotton heterosis. Abstract : We revealed that Chinese upland cotton source germplasm (CUCSG) could be genetically and geographically categorized into three subgroups. The divergence genomic regions among these subgroups were found to be related with both maturity and heterosis. We thus provided new knowledge of genetic diversity for the cultivated upland cottons.